From time-motion analysis to specific intermittent high intensity training - Huey, A.; Morrow, P.; O'Donoghue, P. (5th World Congress of Performance Analysis of Sport, 2001)
A time-motion analysis of 9 male and 9 female hockey players revealed that during a 70 minute match the female players performed 101.3+14.7 bursts of high intensity activity lasting 6.6+1.7s on average, with a mean recovery period of 36.0+6.1s. While the male subjects performed 145.7+31.5 bursts of 4.1+0.5s mean duration with a mean recovery period of 27.0+6.6s. The female subjects spent 15.4+3.7% of the match performing high intensity activity compared with 13.4+2.1% for the male subjects. Many time-motion analysis investigations have recommended specific intermittent high intensity training for field games (McErlean et al, Time-motion analysis of gender and positional effects on work-rate in elite Gaelic football competition, Journal of Human Movement Studies, 38, pp269-286, 2000). The purpose of the current investigation is to determine whether such specific training, based on time-motion analysis results, will improve the fitness of players. Nine female players and 8 male players were placed into an endurance training group (END) that did an 8 week endurance training programme during the pre-season. Ten female players and 8 male players were placed in an intermittent training group (INT) that did an identical 8 week training programme but with one session per week being replaced by a 28 minute intermittent training session composed of 40 repetitions of a 6s high intensity burst (sprinting) followed by a 30s low intensity recovery period (jogging). All subjects were tested before, four weeks into as well as after the eight week experimental period using a multi-stage fitness test, a 40m sprint test and a multiple sprint test of eight 40m sprints with a 30 s recovery. A series of three-way ANOVA's were applied, including group and gender as between subjects effects and test as well as test as a repeated measure. There was no significant interaction between group and test for the results of the multi-stage fitness test (F2,62 = 1.9, P > 0.05), or the multiple sprint test (F2,62 = 0.1, P > 0.05). The interaction of group and test did have a significant influence on the result of the 40m sprint test (F2,62 = 10.3, P < 0.001). Table 1 shows that the 40m sprint time of subjects in the control group were slower after the eight week period than before. Male subjects of the experimental group performed the test faster at the end of the training programme than before. The current results would suggest that although specific intermittent training is not significantly more beneficial than endurance training for aerobic endurance and ability to perform multiple sprints, deterioration in 40m sprint speed can be significantly reduced by intermittent training.